Psychology and cognitive archaeology an interdisciplinary approach to the study of the human mind - Henley, Tracy B.; Rossano, Matthew J. 1962- (Routledge, Taylor & Francis Group, 2022)
"Psychology and Cognitive Archaeology demonstrates the potential of using cognitive archaeology framing to explore key issues in contemporary psychology and other behavioral sciences. This edited volume features psychologists exploring archaeological data concerning specific themes such as: the use of tools, our child-rearing practices, our expressions of gender and sexuality, our sleep patterns, the nature of warfare, cultural practices, and the origins of religion. Other chapters touch on cognitive archaeological methods, the history of evolutionary approaches in psychology, and relevant philosophical considerations to further illustrate the interdisciplinary potential between archaeology and psychology. As a complementary counterpoint, the book also includes an archaeologist's perspective on these same topical matters, as well as robust introductory and concluding thoughts by the editors. This book will be an illuminating read for students and scholars of psychology (particularly theoretical, social, cognitive and evolutionary psychology), as well as philosophy, archaeology, and anthropology"--
Keywords: Psychologie; Kognitive Archäologie; Cognition and culture; Ethnopsychology; Neuroanthropology; Psychology; Archaeology; Material culture / Psychological aspects